Fat nation : a history of obesity in America - Engel, Jonathan (Rowman & Littlefield, 2018)
The estimated annual health care cost of obesity-related illness in the United States is 190 billion, with countless more costs in lost mobility, vigor, and life-years. Here, Jonathan Engel reviews the sources of the problem as they have developed over the past 70 years and offers a realistic plan for helping address obesity.